PENERAPAN PENDEKATAN SAINS TEKNOLOGI MASYARAKAT (STM) UNTUK MENINGKATKAN HASIL BELAJAR IPA SISWA KELAS V A SD NEGERI 034 TARAI BANGUN KECAMATAN TAMBANG - Mira Hartati; Damanhuri Daud; Lazim N Lazim N (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2014)
Abstract: The problem in this study is the low student science learning outcomes, it is seen from the average value is 61.51 students. Of the 39 students who achieve grades above KKM (Minimum Criteria for completeness) is only 17 students (43.59%), while students who have not reached the KKM were 22 students 41%, KKM value specified is 65. based on these problems needs to be done to implement the action research approach of Science Technology Society (STM). This study aims to improve science learning outcomes graders VA SD Negeri 034 Tarai Bangun Academic Year 2013/2014 the number of students a total of 39 people. This research was carried out by three cycles. One Cycle consists of five meetings, in which four face to face meetings and one final cycle repetitions. With the implementation STM, it can improve students' science learning outcomes, it is seen from the percentage of completeness student learning outcomes on the basis that the score of 43.59% (average of 61.51) increased to 71.79% (average of 72.17) in the first cycle and the second cycle increased to 97.44% (average of 77.30), and the third cycle increased to 100% (average of 83.97). Percentage of teacher activity also increased, as seen from the percentage of all teachers in the first cycle 61.1% increase to 80.5% in the second cycle, and increased again in the third cycle is 95.8%. The percentage of student activity also increased from 50% in the first cycle increased to 69.4% in the second cycle and increased again to 93% in the third cycle. From the above it can be seen that the approach of Science Technology Society (STM), can improve learning outcomes IPA student VA SD Negeri 034 Tarai Bangun Kecamatan Tambang.Key words: Approach Science Technology Society (STM), Science Student Learning Outcomes